2015
DOI: 10.1093/eurheartj/ehv301
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospitalization for heart failure in patients with type 2 diabetes newly treated with DPP-4 inhibitors or other oral glucose-lowering medications: a retrospective registry study on 127,555 patients from the Nationwide OsMed Health-DB Database

Abstract: In a very large observational study, the use of DPP-4i was associated with a reduced risk of HHF when compared with sulphonylureas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 29 publications
3
72
1
1
Order By: Relevance
“…With DPP4i some studies showed an increased risk of MI and ischemic stroke [23,[27][28][29] or HF [22]. Contradictingly, other studies have shown a significantly lower HF risk [30] or a neutral effect on CV events [28].…”
Section: Discussionmentioning
confidence: 99%
“…With DPP4i some studies showed an increased risk of MI and ischemic stroke [23,[27][28][29] or HF [22]. Contradictingly, other studies have shown a significantly lower HF risk [30] or a neutral effect on CV events [28].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Diabetic patients with heart failure have an increased mortality and an increased risk of hospitalisations and the use of certain anti-diabetic agents increase the risk of mortality and hospitalisation in heart failure. [4] Conversely, newer therapeutic agents have shown a significant reduction of mortality, morbidity and risk of developing heart failure in diabetic patients with proven cardiovascular disease. [5] Epidemiological evidence clearly shows that diabetes mellitus is independently associated with the risk of developing HF.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Also, the adequate level of glucose control in diabetic patients with heart failure is under debate but higher levels of HbA1c should be recommended for diabetic patients with heart failure. [12] Treatment of heart failure in patients with diabetes…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations